Resource Conflict and Food Security: Implications for Peace-building in Nigeria - VANDE, Philip Terzungwe (Socialscientia: Journal of Social Sciences and Humanities, 2023)
The use of resources, especially land and water has remained a major source of conflict among users of all kinds. Over the years, but more recently, conflict between farmers and herders in the use of the agricultural land and water points has become fiercer and increasingly widespread in Nigeria. The conflict has not only heightened the level of insecurity, but have also demonstrated high potential to exacerbate food crisis in Nigeria, due to loss of lives, animals, destruction of crops and valuable property and forced displacement of sedentary farmers. This study therefore investigated resource conflict and food security in Nigeria. It was based on secondary methods and materials and relied human needs theory as a framework of analysis. The study found that there is a significant relationship between resource conflict, exemplified in the farmer-herder conflict and food security in Nigeria. The study also revealed that there is a significant relationship between farmer-herder conflict and food security in terms of availability of food, accessibility of food and sustainability of food supply in Nigeria. The study recommends the need for government’s intervention to ensure the adoption of modern methods of agricultural practices and animal husbandry. It also recommends for strong political will from governments at all levels in resolving resource conflicts between farmers and herders. These, among others, will resolve the recurring conflict and ensure food security in Nigeria.